Shakespeare and the question of theory - Parker, Patricia A., 1946-; Hartman, Geoffrey H. (Methuen, 1985)
The theoretical ferment which has affected literary studies over the last decade has called into question traditional ways of thinking about, classifying and interpreting texts. Shakespeare has been not just the focus of a variety of divergent critical movements within recent years, but also increasingly the locus of emerging debates within, and with, theory itself. This collection of essays, written by distinguished and powerful critics in the fields of literary theory and Shakespeare studies, is intended both for those interested in Shakespeare and for those interested more generally in the.
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation.; Shakespeare, William, -- 1564-1616 -- Critique et interprétation.; Shakespeare, William, -- 1564-1616; English drama -- History and criticism -- Theory, etc.; Criticism.; Théâtre anglais -- Histoire et critique -- Théorie, etc.; Critique.; literary criticism.; criticism.; LITERARY CRITICISM -- Shakespeare.; DRAMA -- Shakespeare.; Criticism; Drama in English -- Shakespeare, William - Critical studies; Electronic books.; Criticism, interpretation, etc.